2000
DOI: 10.1046/j.1471-4159.2000.0750413.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, Pharmacological, and Molecular Characterization of an Amphibian Cannabinoid Receptor

Abstract: Investigation of cannabinoid pharmacology in a vertebrate with a phylogenetic history distinct from that of mammals may allow better understanding of the physiological significance of cannabinoid neurochemistry. Taricha granulosa, the roughskin newt, was used here to characterize an amphibian cannabinoid receptor. Behavioral experiments demonstrated that the cannabinoid agonist levonantradol inhibits both newt spontaneous locomotor activity and courtship clasping behavior. Inhibition of clasping was dose-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…However, the presence of the CB 1 -selective antagonist AM281 at 1 M (Howlett et al, 2002) blocked the effects of WIN on the frequency and amplitude of the MEPPs, indicating that WIN acts through activation of the CB 1 receptors. These results are accord with only the CB 1 receptor ortholog having reported in amphibians (Soderstrom et al, 2000;McPartland et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the presence of the CB 1 -selective antagonist AM281 at 1 M (Howlett et al, 2002) blocked the effects of WIN on the frequency and amplitude of the MEPPs, indicating that WIN acts through activation of the CB 1 receptors. These results are accord with only the CB 1 receptor ortholog having reported in amphibians (Soderstrom et al, 2000;McPartland et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…These effects are produced by the interaction of these compounds with the cannabinoid membrane receptors named CB 1 and CB 2 (Howlett et al, 2002). Both subtypes of cannabinoid receptors alter cellular activity through activation of G proteins of the G i/o subtype, which are sensitive to pertussis toxin (Soderstrom et al, 2000), although some effects are thought to occur through G s (Bayewitch et al, 1995;Glass and Felder, 1997). Activation of G i/o proteins by CB 1 and CB 2 receptors decreases adenylate cyclase activity, leading to decreased levels of intracellular cyclic AMP and protein phosphorylation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, consistent with the notion that CB 1 has an evolutionarily ancient role in neural pathways that control movement, Valenti et al [97] have reported that the CB 1 receptor antagonist AM 251 (1 mg g 21 body mass) causes a reduction in locomotor activity in the goldfish Carassius auratus. Behavioural effects of drugs that bind to the CB 1 receptor have also been investigated in an amphibian species, the roughskinned newt T. granulosa, revealing an inhibitory effect on spontaneous locomotor activity and courtship clasping behaviour [98]. Likewise, the cannabinoid WIN 55,212-2 causes inhibition of locomotor activity in the zebra finch [99].…”
Section: Comparative Neurobiology Of Endocannabinoid Signallingmentioning
confidence: 99%
“…It is important to determine whether cannabinoid receptors behave like their mammalian equivalents in other species. Thus, for example, the cannabinoid 1 receptor in the roughskin newt (Taricha granulosa) showed considerable structural homology and affinity for cannabinoid ligands to its rodent equivalent (Sö -derströ m et al 2000). In contrast, however, the cannabinoid receptor identified in Drosophila melanogaster in binding studies using [ 3 H]CP 55,940 could not be blocked by SR 141716A or SR 144528 (Howlett et al 2000).…”
mentioning
confidence: 99%